Family history of cancer and germline BRCA2 mutations in sporadic exocrine pancreatic cancer. Issue 5 (1st May 2002) - Real, F X; Malats, N; Lesca, G; Porta, M; Chopin, S; Lenoir, G M; Sinilnikova, O
Abstract : Background: Hereditary factors have been reported in 5–10% of cases with exocrine pancreatic cancer and recent data support a role for BRCA2 . Aims: We have studied the prevalence of germline BRCA2 mutations in two groups of patients with exocrine pancreatic cancer from an unselected series in Spain: group A included 24 cases showing familial aggregation of cancer and group B included 54 age, sex, and hospital matched cases without such evidence. Methods: Information was obtained by interview of patients and was validated by a telephone interview with a structured questionnaire. In patients from group A, >80% of the coding sequence of BRCA2 was analysed; in patients from group B, the regions in which germline BRCA2 mutations have been described to be associated with pancreatic cancer were screened. Results: Telephone interviews led to reclassification of 7/54 cases (13%). Familial aggregation of cancer was found in 24/165 cases (14.5%); six patients had a first degree relative with pancreatic cancer (3.6%) and nine patients had relatives with breast cancer. Germline BRCA2 mutations were not identified in any patient from group A (0/23). Among group B cases, one germline variant (T5868G>Asn1880Lys) was found in a 59 year old male without a family history of cancer. The 6174delT mutation was not found in any of the 71 cases analysed. Conclusions: The overall prevalence of BRCA2 mutations among patients with pancreatic cancer in Spain is low and the 6174delT mutation appears to be very infrequent. Our data do not support screening patients with cancer of the pancreas for germline BRCA2 mutations to identify relatives at high risk of developing this tumour.